2014
DOI: 10.1007/s10753-014-0023-y
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Expression of NLRP1 and IPAF Are Related to Oral Pemphigus Vulgaris Pathogenesis

Abstract: Oral pemphigus vulgaris (PV) is a rare blistering disorder of the skin and mucous membranes in the mouth. Inflammasome serves as a molecular platform that mediates the autoactivation of caspase-1, which cleaves the pro-forms of IL-1β and IL-18 to active forms. Therefore, the main aim of this study was to evaluate the messenger RNA (mRNA) levels of NOD-like receptor-related protein (NLRP)1, NLRP3, and IPAF in the PBMCs of PV patients to determine their effect in PV pathogenesis. This study was designed as a cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In addition, caspase-1 activation may lead to the processing and maturation of IL-1β, thus resulting in allergic symptoms in the sensitized mice. In accordance with these results, a previous study reported that elevated expression of IPAF, alongside IL-1β, is involved in the inflammation of patients with pemphigus vulgaris (33). In addition, Liu and Chan (34) revealed that palmitate was able to induce the production of IL-1β via activation of the IPAF-ASC inflammasome in primary astrocytes.…”
Section: Discussionsupporting
confidence: 81%
“…In addition, caspase-1 activation may lead to the processing and maturation of IL-1β, thus resulting in allergic symptoms in the sensitized mice. In accordance with these results, a previous study reported that elevated expression of IPAF, alongside IL-1β, is involved in the inflammation of patients with pemphigus vulgaris (33). In addition, Liu and Chan (34) revealed that palmitate was able to induce the production of IL-1β via activation of the IPAF-ASC inflammasome in primary astrocytes.…”
Section: Discussionsupporting
confidence: 81%
“…Similar to caspase-5, associated NLRP1 was also suppressed, IL-1β-levels reduced (0.6-fold, p = 0.16), whereas caspase-1 levels remained unaffected (Fig 5H, data not shown). Together, data suggest that targeting caspase-5 may contribute to the anti-inflammatory effects of vitamin D that could be relevant for treatment of Th17-mediated autoinflammatory diseases with caspase-5 overexpression, such as psoriasis or lupus erythematosus (S4 Fig, S5 Fig), or others with proposed NLRP1 inflammasome activity[20, 21]. …”
Section: Resultsmentioning
confidence: 99%
“…Increasing evidence connects the NLRP1 inflammasome to the pathogenesis of skin-associated autoimmune diseases, such as vitiligo, lupus erythematosus, pemphigus vulgaris, and psoriasis [15, 17, 20, 45]. Compared to other inflammasome complexes, such as NLPR3 and AIM2 expressed in keratinocytes, NLRP1 can activate caspase-5 besides inflammasome ubiquitous caspase-1 [8, 11].…”
Section: Discussionmentioning
confidence: 99%
“…Also, several studies have demonstrated the differences between sera cytokines levels of pemphigus patients and healthy controls (systematically reviewed by Tavakolpour et al 9 ), while there are limited reports regarding different genes' expression profile in comparison with healthy controls. The expression of NLRP1 , 10 IPAF , 10 CD19 genes, 11 and some miRNAs including miR‐424‐5p 12 and miRNA‐338‐3p 13 were demonstrated to be significantly increased in blood samples of PV and/or PF patients. Moreover, overexpression of IL17 and IL23 genes were reported to be occurred in lesion biopsy samples of pemphigus patients 14 .…”
Section: Introductionmentioning
confidence: 98%